The relationship between servitization and product customization strategies. Issue 3 (3rd May 2019) - Sousa, Rui; da Silveira, Giovani J.C.
Abstract : Purpose: The purpose of this paper is to examine the relationship between product customization and servitization strategies, specifically the relationship between product customization strategy intensity and degree of servitization (offering of basic and/or advanced services) and the moderating role of product customization strategy alignment on that relationship. Design/methodology/approach: The authors develop and test hypotheses through partial least squares path modeling to analyze data from the Sixth International Manufacturing Strategy Survey, involving 931 manufacturers in 22 countries. Findings: The results indicate that customization strategy intensity is positively associated with the offering of basic and advanced services; these relationships are not moderated by customization strategy alignment. Practical implications: Manufacturers pursuing product customization strategies may be especially well positioned to servitize, even those with misalignment in strategic choices. Paradoxically, while manufacturers of standard products might look at servitization as an attractive strategy to differentiate their value proposition, they appear to be less servitized than manufacturers pursuing product customization. Originality/value: This is one of the first studies to examine how manufacturing strategy choices (intensity and alignment) influence the adoption of servitization strategies. The study introduces manufacturing strategy as a contingency factor that influences the adoption of servitization, answering calls for the study of servitization contingencies.